The relationship between spousal empowerment, quality of life, and subjective wellbeing among disabled elderly - Fei Ye; Yuanrong Wu; Chao Pan; Zifen An; Yanzhen Zhai; Dan Wang; Liping Yu; Yanni Zhu (Frontiers in Psychology)
BackgroundAs rapidly ages, the number of disabled elderly is increasing, leading to lower quality of life and greater psychological stress.AimTo explore the relationship between spousal empowerment, quality of life, and subjective wellbeing (SWB) among disabled elderly, providing insights and practical guidance for enhancing SWB in this demographic.MethodA convenience sampling approach was employed to select 332 disabled elderly and their spouses. Research tools included a demographic survey, the Barthel Index (BI), the World Health Organization Quality of Life Assessment - Older Adults Version (WHOQOL-OLD), the Memorial University of Newfoundland Scale of Happiness (MUNSH), and the Main Caregivers’ Empowerment Measurement (MCEM). Statistical analysis was performed using SPSS and AMOS.ResultThe mean scores for the quality of life, SWB, and spousal empowerment were 72.07 ± 19.79, 24.13 ± 8.98, and 140.92 ± 29.13. Multiple linear regression analysis identified spousal empowerment (β = 0.258, p < 0.001) and the duration of disability (β = −0.142, p = 0.032) as significant predictors of SWB. The results of testing the mediating role of spousal empowerment using the structural equation model show that quality of life directly predicted SWB with a path coefficient of 0.208 (95% CI: 0.065, 0.289). Spousal empowerment partially mediated the relationship between quality of life and SWB, with a mediation effect of 0.067 (95% CI: 0.026, 0.098).ConclusionBoth quality of life and spousal empowerment can positively influence the SWB of disabled elderly. Additionally, spousal empowerment partially mediates the relationship between quality of life and SWB.